Bestari Partners - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2019)
PAPER WRITTING STIPULATIONPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.- Papers must be a real work of the author.- Papers has never been published in other media.- Papers contain discussion about Infrastructure & Facility Asset Management.- Papers contains a new discussion, judging based on the discussion that has been published on JIFAM.- The paper have to take a reference from JIFAM/JMAIF for at least 1 paper and from outside JIFAM a minimum of 1 paper.- Paper lengths are limited in 8-16 pages.- Paper writing format can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifam.TOPIC SCOPEJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of  the following.- I & F Function- I & F Demand - Supply- I & F User Behavior- I & F Policy- I & F Planning- I & F Administration Aspects- I & F Operation System- I & F Maintenance System- I & F Evaluation Technique- I & F Disposal- I & F Economical Aspect- I & F Financial Aspect- I & F Management Organization- I & F Spatial Aspects and Environmental AspectsREVIEWERHitapriya Suprayitno, Institut Teknologi Sepuluh Nopember (ITS), Surabaya.Ria Asih Aryani Soemitro,  Institut Teknologi Sepuluh Nopember (ITS), Surabaya.Data Iranata, Institut Teknologi Sepuluh Nopember (ITS), Surabaya.